PENINGKATAN AKTIVITAS SISWA MELALUI PENDEKATAN MATEMATIKA REALISTIK PADA MATERI KESEBANGUNAN DI KELAS IX B SMP NEGERI 1 SAMALANTAN - Mujiarso, J (Jurnal Pendidikan Matematika dan IPA, 2014)
The aim of this research was to improve students' learning activities through realistic mathematical approaches in class IX B Junior High School Negeri 1 Samalantan in academic year of  2014/2015. The form of this research was classroom action research (CAR). The subjects in this study were the students of class IX B consisting of 34 students. The instrument of this research used  the observation sheet and field notes. The results showed that an increase in the activity after the students were given a realistic mathematical approach on the material similarity. Based on the analysis of the data obtained the increased activity of the students at 11.776% after implementation realistic mathematics approach in two cycles of the action. Students’ activities in asking questions increased by 13.7%. Students’ activities in answering questions increased from 75.49% to 79.4%. While the activity of students in a discussion group increased by 9.81%. Key words: Students’ activities, realistic mathematics approach, similarity.